Correlation of Smoked Fish Physical Quality and Facilities of Hygiene Activity and Sanitation with the Existence of Escherichia coli Bacteria in Smoked Fish - Refri Fitria Rohmatin Shofuro Setiyono (JURNAL KESEHATAN LINGKUNGAN, 2019)
Fish smoking industry is one of way of fish preservation so that fresh fish have long saving period and always in a good condition. The treatment of smoked fish that is still simple and not processed properly cause the occurence of bacteria in smoked fish product. Escherichia coli bacteria, if exists in food will cause society health problem. This research is to identify the relationship of smoked fish physical quality and facilities of hygiene activity and sanitation with the existence of Escherichia coli bacteria in smoked fish products. This research is analytical that used cross-sectional research period. The sampling technique used simple random sampling. The independent variables studied are smoked fish physical quality and facilities of hygiene and sanitation, while the dependent variable is the existence of Escherichia coli bacteria in smoked fish products. The primary data was processed through observation and questionnaire sheets. The measurement of Escherichia coli bacteria used Escherichia coli qualitative test at Health Laboratory Center Surabaya City. Based on  fisher's exact test dand phi correlation coefficient, The smoked fish physical quality have  (p=0,003, Q=-0,644) and facilties of hygiene activity and sanitation have (p=0,001, Q=-0,730)  has a tight relationship to the emergence of Escherichia coli bacteria in smoked fish products.. The recomended that smoked fish traders and village officials to discuss on the relocation plan of the smoked home industry in permanent buildings and the handler should always maintain the cleanliness of product environment roast fresh fish until it is fully cooked and focus to the ways of marketing smoked fish.